AN OVERVIEW OF SALIVARY INTERLEUKIN-1 AS A BIOMARKER FOR PERIODONTITIS - Zaeem Arif Abbasi; Naila Hadi; Ayesha Tariq Niaz (ziauddin University, 2024)
Periodontitis is a chronic inflammatory condition characterized by destruction of the periodontal tissues resulting in loss of connective tissue attachment and alveolar bone, with formation of pathological pockets around the affected teeth. In recent times, salivary diagnostic tests are becoming popular as saliva is an easily accessible source for detecting several chemokines and cytokines related to various oral pathologies. Moreover, this may also help in detecting periodontitis before the appearance of clinical effects, after which treatment becomes difficult. Many cytokines and chemokines related to periodontal tissue destructionare found in saliva. Though majorly produced in gingival crevicular fluid(GCF), these chemicals eventually leech out to become part of the saliva. Interluekin-1 beta (IL-1β), generated through immune response is considered to be one of the most important cytokine that has detrimental effects on the periodontal tissues. This paper aims to convey an extensive overview regarding the role of salivary IL-1β in periodontitis.